PANDANGAN ORANG TUA TERHADAP ANAK PUTUS SEKOLAH DI TINGKAT SD DESA SUNGAI BULUH KECAMATAN BUNUT KABUPATEN PELALAWAN - Fitri Handayani; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Provide motivation on the child then the child will be lazy for the school. factors that affect the commercial school children that parental education is low, and the lack of interest in the environmental conditions that do not care about the education the purpose of this research is to find out how to view the parent of child education and factors that affect children's school the present breakdown in SD River village of Bunut Pelalawan District Reed. This study used quantitative methods by means of data retrieval in the village of River Reeds in the Sub-District of Bunut. To find out the number of residents in the village of river Reeds and the number of children dropping out of school in SD 009 used census methods that take a whole child who dropped out of school as a sample to assign respondents involved in this research. Data field which became population totaled 18 people consisting of 7 persons class 2 and class 3 to 11. To collect data from respondents in the use of direct observation methods, interview and documentation, for the processing of data on the use of quantitative methods. The respondents in this study generally have middle income and above this should make the motivation for parents to send their children. As an always evolving beings should make the parents being dissatisfied with the child's education. Parents should have a good view of the education of the child so that the child can compete in the future. The development of the present demands of higher education without education then the person will not get any role in his life, from which parents should make sure children have a college education by changing the way parents point of view. View the parent who looks weak from a lack of parental control to his son by not often reminds the child to school. If the child is not guided properly, then the child will loose control and will likely not have any interest to the school. parents should also complement the facilities studied children so that children can complete his duties, if the parents do not complement the facilities studied child then the child will not be able to expand rapidly in the lesson. Weak parental view is also visible from the weakness in motivating the child, if the parents are not.Keywords: views of parents, dropping out of school, River Reeds.